Turkey's EU accession as a factor in the 2016 Brexit referendum. (1st January 2018) - Ker-Lindsay, James
ABSTRACT: In June 2016, the UK voted to leave the European Union (EU). Although many issues shaped the Brexit campaign, the question of Turkey's quest for EU membership emerged as an unexpectedly strong factor. This article examines how this happened and how the debate evolved. It shows that those who advocated leaving the EU not only distorted the prospect of Turkish membership, they also misrepresented British support for the country's accession. While the UK had indeed been a strong advocate of Turkey's EU integration in the past, support for enlargement in general had declined in recent years due to increasing voter concerns over immigration. However, the policy of supporting Turkish membership could not be wholly repudiated by the government, even in the name of campaigning to stay in the EU, as this would have damaged Britain's strategic relationship with Turkey.